2014
DOI: 10.1016/j.aquaculture.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Vertical movement of spawning cultured chub mackerel (Scomber japonicus) in a net-cage

Abstract: Vertical behavior of cultured chub mackerel, Scomber japonicus, in a net-cage was investigated using depth data logger and infrared video camera footage during the spawning and non-spawning seasons. Marked differences in the vertical distributions of spawning and non-spawning mackerel were observed. Non-spawning mackerel swam near the bottom of the net-cage during the daytime, coming up to shallow waters during night-time. However, spawning mackerel remained near the bottom of the net at all times except for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For fish with a swim bladder, their volume has a greater effect on TS than g and h values (Mukai and Iida, 1996;Gorska and Ona, 2003). Studies showed that some mackerel species have a diel vertical migration behavior (Bertrand et al, 2004;Li et al, 2014;Tsuda et al, 2014;Paramo et al, 2015). They usually aggregate in deeper water during the daytime and move to the surface at night.…”
Section: Discussionmentioning
confidence: 99%
“…For fish with a swim bladder, their volume has a greater effect on TS than g and h values (Mukai and Iida, 1996;Gorska and Ona, 2003). Studies showed that some mackerel species have a diel vertical migration behavior (Bertrand et al, 2004;Li et al, 2014;Tsuda et al, 2014;Paramo et al, 2015). They usually aggregate in deeper water during the daytime and move to the surface at night.…”
Section: Discussionmentioning
confidence: 99%
“…Chub mackerel, Somber japonicus, is a typical marine pelagic fish widely distributed in the North Pacific and North Atlantic Oceans [15]. In China, this species plays an irreplaceable role in Chinese food culture and also has been previously reported as a keystone species in the Yellow Sea food web [9].…”
Section: Introductionmentioning
confidence: 99%